KERUKUNAN DALAM KEANEKARAGAMAN: Struktur Keberagamaan Masyarakat Pucakwangi - Mas'udi, Mas'udi (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2018)
This study aims to determine the religious structure of the community of Pucakwangi Village, Pucakwangi District, Pati Regency, Central Java Province. Religious awareness is an important foundation for the formation of religious harmony in diversity. With a qualitative functional structural approach, this study analyzes the structures that form community harmony in its diversity. The results of the study show some basic structures found in the midst of the diversity of the Pucakwangi Village community. Building an attitude of sympathy among followers of religion created with the participation of Christians in